Mengaplikasikan Komunikasi dalam Keberhasilan pada Dunia Kerja - Septya Suarja; Arman Bin Anuar; Alfaiz Alfaiz; Triyono (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2022)
Applying communication for success in the world of work is a Padang Vocational Training Center (BLK) program that aims to increase or improve knowledge, skills, attitude and work experience for trainees at Padang BLK. The activity method is carried out by way of workshops, lectures and questions and answers which will be held from June 8 2021 to June 9 2021. The scope of this activity is carried out at the BLK Padang Office with a schedule that has been coordinated with the committee and the soft skills team. The results of this activity indicate an increase in knowledge and attitude skills and work experience for the trainees. In addition to providing material, the training participants are equipped with communication skills and preparation for entering the world of work, both from making cover letters, facing interviews and how to communicate with superiors.